474O Efficacy and safety of first-line durvalumab (D) ± tremelimumab (T) vs chemotherapy (CT) in Asian patients with metastatic NSCLC: Results from MYSTIC. (24th November 2019) - Cho, B C; Lee, K H; Ahn, M-J; Geater, S Lucien; Ngoc, T V; Wang, C-C; Cho, E K; Lee, J S; Sriuranpong, V; Bui, Q; Clarke, S; Kuyama, S; et al.
Abstract: Background: In MYSTIC, an open-label, phase 3 trial of first-line D (anti-PD-L1) ± T (anti-CTLA-4) vs CT, while not statistically significant, a clinically meaningful improvement in overall survival (OS) was seen with D vs CT in patients with tumour cell PD-L1 expression ≥25% (TC ≥ 25% [primary analysis population]; D vs CT, HR 0.76 [97.54% CI 0.56–1.02]; D+T vs CT, HR 0.85 [98.77% CI 0.61–1.17]). Here we report results in a subpopulation of Asian patients. Methods: Immunotherapy/CT-naïve patients with metastatic NSCLC were randomized (1:1:1) to D (20 mg/kg q4w); D (20 mg/kg q4w) + T (1 mg/kg q4w ≤4 doses); or CT. In this analysis in a subpopulation of Asian patients, efficacy outcomes were evaluated in patients with PD-L1 TC ≥25%; safety was evaluated in all treated patients (regardless of PD-L1 expression). Results: Of the 488 patients in the primary analysis population (PD-L1 TC ≥25%), 156 (32%) were Asian (D, 59; D+T, 50; CT, 47). Baseline characteristics in the Asian population were balanced between treatment arms. OS was improved in Asian patients (PD-L1 TC ≥25%) with D vs CT (HR 0.69 [95% CI 0.43–1.09]) and D+T vs CT (HR 0.64 [95% CI 0.40-1.03]); more patients receiving D or D+T remained in response at 6 months vs CT (Table). Grade ≥3 treatment-related adverse events (TRAEs) and any grade TRAEs leading to discontinuation occurred in 19.7% and 9.0% (D); 23.9% and 14.5% (D+T); 23.4% and 7.2% (CT) patients in the Asian subpopulation, respectively. Conclusions: Durvalumab resulted in a favourable HR for OS compared to CT in patients with PD-L1 TC≥25% in the Asian subpopulation, which was consistent with the primary analysis population. OS HR for D+T vs CT appeared to be more favourable in the Asian subpopulation compared to the primary analysis population, although results should be interpreted with caution due to small sample sizes. The safety profile of D±T in the subpopulation of Asian patients was manageable and consistent with the primary analysis population. Clinical trial identification: NCT02453282. Editorial acknowledgement: Medical writing support, which was in accordance with Good Publication Practice (GPP3) guidelines, was provided by Beena John, PhD of Cirrus Communications (Macclesfield, UK), an Ashfield company, and was funded by AstraZeneca. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: B.C. Cho: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): MOGAM Institute; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Roche; Advisory / Consultancy: BMS; Advisory / Consultancy, Research grant / Funding (institution): Ono; Advisory / Consultancy, Research grant / Funding (institution): Yuhan; Advisory / Consultancy, Research grant / Funding (institution): Janssen; Research grant / Funding (institution): Champions Oncology; Research grant / Funding (institution): Dong-A ST; Research grant / Funding (institution): Dizal Pharma; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Takeda; Shareholder / Stockholder / Stock options: TheraCanVac Inc. K.H. Lee: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: BMS. S. Lucien Geater: Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Samsung. T.V. Ngoc: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Novartis. S. Clarke: Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca. S. Kuyama: Speaker Bureau / Expert testimony, Lecture fees: AstraZeneca; Speaker Bureau / Expert testimony, Lecture fees: Pfizer; Speaker Bureau / Expert testimony, Lecture fees: Eli Lilly; Speaker Bureau / Expert testimony, Lecture fees: Boehringer Ingelheim; Speaker Bureau / Expert testimony, Lecture fees: MSD; Speaker Bureau / Expert testimony, Lecture fees: Taiho; Speaker Bureau / Expert testimony, Lecture fees: Chughai. K. Nakagawa: Honoraria (institution), Research grant / Funding (institution): MSD / Takeda / SymBio Pharmaceuticals / Daiichi Sankyo; Honoraria (self), Research grant / Funding (institution): Eli Lilly Japan; Honoraria (self), Research grant / Funding (institution): BMS; Honoraria (self), Research grant / Funding (institution): Taiho /Ono / Chughai; Honoraria (self), Research grant / Funding (institution): AstraZeneca / Astellas Pharma / Novartis / Nippon Boehringer Ingelheim / Pfizer Japan; Research grant / Funding (institution): Merck Serono / ICON Japan /PAREXEL / IQVIA Services Japan / A2 Healthcare / AbbVie; Research grant / Funding (institution): EP-CRSU / Linical / Otsuka Pharmaceuticals / EPS International / Quintiles / CMIC Shift Zero / Eisai / Kissei Pharmaceutical ; Research grant / Funding (institution): Kyowa Hakko Kirin / EPS Corporation / Bayer Yakuhin / inVentiv Health Japan / Gritstone Oncology / GSK / Yakult Honsha / Covance ; Honoraria (self): Kyorin Pharmaceutical / CareNet / Nichi-Iko Pharmaceutical / Hisamitsu Pharmaceutical / Yodosha / Clinical Trial / Reno Medical / Nanzando / Medical Review; Honoraria (self): Medicus Shuppan / Ayumi Pharmaceutical / Thermo Fisher Scientific / Yomiuri Telecasting Corporation / Nikkei Business Publications. F. Liu: Full / Part-time employment, Full-time employee: AstraZeneca. D. Clemett: Full / Part-time employment, Full-time employee: AstraZeneca. U. Scheuring: Full / Part-time employment, Full-time employee: AstraZeneca. S. Peters: Honoraria (self), Advisory / Consultancy: AbbVie; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Amgen; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): AstraZeneca / Pfizer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Bayer / Seattle Genetics and Takeda; Honoraria (self), Advisory / Consultancy: Biocartis; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): BMS; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Clovis; Honoraria (self), Advisory / Consultancy: Daiichi Sankyo / Regeneron / Sanofi; Honoraria (self), Advisory / Consultancy: Debiopharm; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): F Hoffmann-La Roche; Honoraria (self), Advisory / Consultancy: Foundation Medicine; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Illumina; Honoraria (self), Advisory / Consultancy: Janssen; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Merck Sharp & Dohme; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Merck Serono; Honoraria (self), Advisory / Consultancy: Merrimack; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Honoraria (self), Advisory / Consultancy: Pharma Mar. N. Rizvi: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Novartis; Advisory / Consultancy: Merck Sharp & Dohme; Advisory / Consultancy: BMS; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Lilly; Advisory / Consultancy: AbbVie; Advisory / Consultancy: Regeneron; Advisory / Consultancy: Janssen; Leadership role, Shareholder / Stockholder / Stock options: ARMO BioSciences; Shareholder / Stockholder / Stock options: Gritstone Oncology. All other authors have declared no conflicts of interest.